Circulating FABP-4 Levels in Patients with Atherosclerosis or Coronary Artery Disease: A Comprehensive Systematic Review and Meta-Analysis - Narges Jalilian; Reza Pakzad; Mahdi Shahbazi; Seyyed-Reza Edrisi; Karimeh Haghani; Mohsen Jalilian; Salar Bakhtiyari (Hindawi-Wiley, 2023)
Background. Cardiovascular diseases (CDs), notably coronary artery disease (CAD) due to atherosclerosis, impose substantial global health and economic burdens. Fatty acid-binding proteins (FABPs), including FABP-4, have been recently linked to CDs. This study conducted a systematic review and meta-analysis to examine FABP-4 levels in CAD and atherosclerosis patients, exploring their potential links to these conditions. Methods. A systematic review and meta-analysis were done based on the PRISMA guideline. The international databases including Medline, Embase, Cochrane Library, Scopus, Web of Science, and UpToDate were searched to find all related studies on the effect of FABP-4 on patients with CAD or atherosclerosis which were published till June 2022 without language restriction. The Cochran's Q-test and I2 statistic were applied to assess heterogeneity, a random effect model was used to estimate the pooled standardized mean difference (SMD), a metaregression method was utilized to investigate the factors affecting heterogeneity between studies, and Egger's test was used to assess the publication bias. Results. Of 1051 studies, 9 studies with a sample size of 2327 were included in the systematic review and meta-analysis. The level of circulating FABP-4 in the patient groups was significantly higher than in the control groups (SMD=0.60 (95% CI: 0.30 to 0.91, I2: 91.47%)). The SMD in female and male patients were 0.26 (95% CI: 0.01 to 0.52, I2: 0%) and 0.22 (95% CI: 0.08 to 0.35, I2: 44.7%), respectively. There was considerable heterogeneity between the studies. The countries had a positive relationship with heterogeneity (coefficient=0.29, p<0.001); but BMI, lipid indices, gender, study design, and type of kit had no effect on the heterogeneity. No publication bias was observed (p: 0.137). Conclusion. In summary, this meta-analysis revealed elevated circulating FABP-4 levels in CDs, suggesting its potential as a biomarker for these conditions. Further research is warranted to explore its clinical relevance.